Expert Oracle9i Database Administration - Alapati, Sam R. (Apress, 2012)
How to Become an Oracle DBA Currently, you have several ways to become a proficient Oracle DBA. First, you can take the whole series of Oracle classes, each of which lasts between 3 and 5 working days. You have to take all of these classes just to be able to perform the basic DBA duties. In addition, you need to peruse the Oracle manuals—there's an entire library of books that Oracle gives away freely on CD and on its Web site. Lastly, you may also wish to purchase books published by private publishers that impart various pieces of the knowledge it takes to become an accomplished Oracle DBA. Oh, and don't forget, you'll also need to acquire the necessary operating system knowledge somewhere. Because most of the large databases using Oracle are based on the UNIX (or Linux) operating system, you'll need to have a reasonably good understanding of UNIX. You can gain this understanding either by attending a class or two from the leading UNIX system vendors such as Hewlett-Packard and Sun Microsystems or by reading manuals and/or books about UNIX published by independent companies.